Blood‐Catalyzed RAFT Polymerization. (12th July 2018) - Reyhani, Amin; Nothling, Mitchell D.; Ranji‐Burachaloo, Hadi; McKenzie, Thomas G.; Fu, Qiang; Tan, Shereen; Bryant, Gary; Qiao, Greg G.
Abstract: The use of hemoglobin (Hb) contained within red blood cells to drive a controlled radical polymerization via a reversible addition‐fragmentation chain transfer (RAFT) process is reported for the first time. No pre‐treatment of the Hb or cells was required prior to their use as polymerization catalysts, indicating the potential for synthetic engineering in complex biological microenvironments without the need for ex vivo techniques. Owing to the naturally occurring prevalence of the reagents employed in the catalytic system (Hb and hydrogen peroxide), this approach may facilitate the development of new strategies for in vivo cell engineering with synthetic macromolecules.